Verification of the computer model of the bus rollover according to Annex 9 UNECE R66 - Razali, Nur Isnida; Abdul Aziz, Nuraini; Topa, Ameen (Penerbit UTM Press, 2025)
An increased use of simulation models to solve problems and assist in decision making has led to a doubt on how to access the confidence of the simulation and modelling. Thus, the simulation models are in dire to be verified. Verification is a process of checking the accuracy of the simulation model by comparing with the known solutions. In this study, the computer model of the bus rollover according to Annex 9 UNECE R66 is verified using two methods which is mesh convergence analysis and through the energy balance and ratio. In mesh convergence analysis, it is important to choose the suitable size of the element of the bus superstructure to be used in the simulation to ensure that the bus structure is not too soft or too rigid. Three elements across the ring pillars of 50x50mm square hollow section (SHS) is chosen based on the intrusion into residual space and the amount of the internal energy absorbed. Energy ratio is the ratio of input energy to output which is total energy and must be in the range of 1.00+/-0.07. The energy ratio obtained is between 0.963 to 1.0148 in this study.